On the endangered languages of modern China. - Serikkaliyeva., А. E.; Abdiman., G. O. (Journal of Oriental Studies, 2016)
This article considers the problem of endangered languages around the world, specially reviewed the situation in China, the causes of this trend, and concrete solutions of the PRC government to preserve endangered languages. This article lists the most endangered languages and the parameters by which language is recognized as endangered.